Beyond the jobs-versus-environment dilemma? Contested social-ecological transformations in the automotive industry. (September 2021) - Pichler, Melanie; Krenmayr, Nora; Maneka, Danyal; Brand, Ulrich; Högelsberger, Heinz; Wissen, Markus
Graphical abstract: Highlights: Mobility transformations require change in the political economy of producing – rather than just the consumption and use of – cars. The role of labor and the visions of workers are so far neglected in research on the transformation of the automotive industry. The political economy of the automotive industry interacts with workers' crisis construals and imaginaries that tend to envision incremental change. Mobilizing workers' knowledge and expertise could support and strengthen legitimacy for more transformative change. Abstract: The transport sector is the major contributor to accelerating CO2 emissions, with the highest proportion stemming from road transport and passenger cars. At the same time, the automotive industry drives economic growth, contributes to state revenues and is an important employer. This article departs from this so-called jobs-versus-environment dilemma to discuss barriers and potentials for transformative change in the Austrian automotive (supplier) industry with a special focus on workers and trade unions. Based on a Cultural Political Economy perspective, we firstly analyze the materiality of the Austrian automotive industry and secondly link these structural features to meaning-making and the articulation of crisis construals and imaginaries by workers and their representatives. This analysis helps to better understand the challenges for more transformative change but thirdly also to examine entry points for such a transformation from a labor perspective. We characterize the materiality of the Austrian automotive industry around six interconnected features and identify an improvement, a diversification and a transformation imaginary. Despite a widespread perception of incremental change among the workforce in the automotive industry, we find that there is strong confidence in their knowledge and expertise that could also support a more systemic mobility transformation. As such, the transformation of the Austrian automotive industry exemplifies both the strategic dilemmas and potentials of social-ecological transformations.